2005
DOI: 10.1016/s0002-9440(10)61250-3
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Tumor Necrosis Factor Confers Partial Protection to Listeria Infection

Abstract: Tumor necrosis factor (TNF) plays a critical role in the host response to the intracellular pathogen Listeria monocytogenes (LM). TNF exists in soluble and membrane-bound forms and exhibits both unique and overlapping activities. We examined the role of membrane TNF in the absence of secreted TNF for host resistance in knockin mice in which the endogenous TNF was replaced by a regulated, noncleavable allele (mem-TNF). Macrophages expressing mem-TNF produced nitric oxide and displayed normal bactericidal activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
44
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 44 publications
(65 reference statements)
3
44
0
1
Order By: Relevance
“…These latter mice can still form compact granulomas, which prevent bacterial spreading, whereas mice completely lacking TNF-␣ are severely impaired in granuloma formation. Expression of a functional transmembrane form of TNF-␣ also confers partial protection to L. monocytogenes infection (28,29), whereas TNF-␣-or TNF-RIdeficient mice are highly susceptible (16, 29 -31).…”
Section: Discussionmentioning
confidence: 99%
“…These latter mice can still form compact granulomas, which prevent bacterial spreading, whereas mice completely lacking TNF-␣ are severely impaired in granuloma formation. Expression of a functional transmembrane form of TNF-␣ also confers partial protection to L. monocytogenes infection (28,29), whereas TNF-␣-or TNF-RIdeficient mice are highly susceptible (16, 29 -31).…”
Section: Discussionmentioning
confidence: 99%
“…The mTNF Á/Á mice were generated by replacing the endogenous TNF allele with the Á1-9, K11E TNF allele. This combined deletion/mutation guarantees loss of TACE-mediated cleavage preventing shedding of solTNF, 19,43 but maintains normal cell-surface expression and function of mTNF. 19 We show that transgenic mTNF Á/Á mice have no abnormal behavioral or histopathological phenotypes when compared to mTNF wt/wt wild-type (WT) littermates.…”
Section: Introductionmentioning
confidence: 99%
“…A recent report using memTNF D1-9,K11E mutant mice indicated that tmTNF is sufficient to provide acute but not longterm control of Mycobacterium tuberculosis infection [44]. The same mutant strain of mice was also reported to be partially protected from LM infection [58]. Interestingly, in the present study, despite the reported partial deficiency of the tmTNF D1-12 mutant in activation of the p55TNFR in cellular assays (as described in [36]), mutant Tnf tm/tm mice also appear to be significantly protected from LM infections, especially following more physiological doses of bacteria (e.g.…”
mentioning
confidence: 97%